2010
DOI: 10.1007/s12032-010-9704-z
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the renal pelvis associated with kidney stones: a case report

Abstract: A 70-year-old female with a long-standing history of kidney calculi presented with vague abdominal pain. Work-up included a CT and MRI of the kidneys. A mass was demonstrated in the superior pole of the left kidney. The mass was biopsied percutaneously under CT guidance. Pathology revealed a poorly differentiated carcinoma, but was inconclusive for a definitive cell type. The patient subsequently underwent a nephrectomy that revealed squamous cell carcinoma of the renal collecting system. She had an uneventful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…Staghorn calculi are most frequently associated with renal pelvis squamous cell carcinoma. [2,5,8] In present case renal squamous cell carcinoma associated with renal calculi, correlated with data given in literature.…”
Section: Dıscussıonsupporting
confidence: 76%
See 2 more Smart Citations
“…Staghorn calculi are most frequently associated with renal pelvis squamous cell carcinoma. [2,5,8] In present case renal squamous cell carcinoma associated with renal calculi, correlated with data given in literature.…”
Section: Dıscussıonsupporting
confidence: 76%
“…[1][2][3][4][5]7,8] The etiological factors which play in the genesis of this rare malignancy are strongly associated with phenacetin consumption, chronic renal calculi, pyelonephritis and squamous metaplasia. [8] Li MK et al in their study reported incidence of coexisting renal stone in 100% cases.…”
Section: Dıscussıonmentioning
confidence: 99%
See 1 more Smart Citation
“…Squamous cell carcinomas have been associated with antecedent calculi or chronic infection. 5 In Japan, the number of deaths as a result of renal pelvic tumors went from 1281 in 2002 to 1200 in 2006 and 1558 in 2010. Similarly, the number of deaths as a result of a ureteral tumor also showed an increasing trend with 1055 in 2006 and 1593 in 2010, compared with 852 in 2002.…”
Section: Upper Tract Urothelial Carcinomamentioning
confidence: 99%
“…2 However, the present histologic and radiologic features of left renal pelvis tumor, including the tumor growth pattern, chronic urothelial inflammatory change, and presence of urinary caliculus inside the renal pelvic tumor, still suggested the probable etiology of primary renal pelvic squamous cell carcinoma. [3][4][5] The current case presents squamous cell carcinomas in 2 visceral organs simultaneously. However, the renal pelvic tumor in the current case can be a primary or metastatic tumor, although the incidences of both the circumstances are believed to be rare.…”
Section: Figurementioning
confidence: 75%